2018
DOI: 10.12688/f1000research.15065.1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic interventions for acute complete ruptures of the ulnar collateral ligament of the thumb: a systematic review

Abstract: Background: The aim of this study was to evaluate the effectiveness of interventions for acute complete rupture of the ulnar collateral ligament (UCL) of the thumb in adults. Methods: The following databases were searched: MEDLINE and EMBASE via OVID, CINAHL and SPORTDiscus via EBSCO, from database inception to 31 st January 2018. Inclusion criteria were: (i) randomised controlled clinical trials (RCTs) or study of intervention with a comparator; (ii) participants with diagnosis of acute complete rupture of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Furthermore, key information errors were found in two review protocols, confusing the exposure and outcome subgroup leading to a lack of clarity [24,27]. Other errors were discovered including the fact that protocols did not provide the details of the search strategy, despite the fact that the published review [34] stated explicitly that the detailed search strategy could be found in the protocol.…”
Section: The Results Of Comparisonmentioning
confidence: 99%
“…Furthermore, key information errors were found in two review protocols, confusing the exposure and outcome subgroup leading to a lack of clarity [24,27]. Other errors were discovered including the fact that protocols did not provide the details of the search strategy, despite the fact that the published review [34] stated explicitly that the detailed search strategy could be found in the protocol.…”
Section: The Results Of Comparisonmentioning
confidence: 99%
“…Termed the 'quasi- Stener' by Milner et al (2015) the study demonstrated that 90% of these injuries fail conservative management and require surgical repair (Milner et al, 2015). Interestingly, a recent systematic review from our institution has shown limited evidence and consensus on the treatment of full-thickness UCL injuries (Mikhail et al, 2018). Further research is required to determine if specific imaging features on MRI could play a role in therapeutic stratification, beyond the position of the torn UCL relative to the aponeurosis.…”
Section: Discussionmentioning
confidence: 99%
“…Complete tears without an associated Stener lesion or associated avulsion fractures represent more of a gray area (35,38,39). In a recent systematic review, no prospective studies comparing outcomes of nonoperative treatment to surgery for complete tears could be found (40).…”
Section: Nonoperativementioning
confidence: 99%